BCT: An Efficient and Fault Tolerance Blockchain Consensus Transform Mechanism for IoT - Fu, Jintian; Zhang, Lupeng; Wang, Leixin; Li, Fengqi (IEEE internet of things journal, 2023)
With the vigorous development of 5G communication technology, massive Internet of Things (IoT) devices generate data incrementally. Different data owners control different private domains of the IoT through edge devices and hope to achieve credible data sharing. Most of the existing solutions are based on blockchain to realize cross-domain IoT data sharing. However, incremental IoT data sharing has dual requirements for the consensus mechanism to be efficient and Byzantine fault tolerant. The independent use of the existing consensus mechanism cannot meet the above requirements simultaneously. Therefore, we propose an efficient and fault-tolerant blockchain consensus transform (BCT) mechanism for IoT. In addition, we design two consensus algorithms, namely, detectable RAFT (DRAFT) and double-layer parallel BFT (DPBFT), to improve the efficiency and fault tolerance of the data-sharing process. Extensive experiments have been conducted to show the efficiency and tolerance of our BCT mechanism.